Rodents: food or pests in Neolithic Orkney - László Bartosiewicz; Andrzej A. Romaniuk; David Clarke; Alexandra N. Shepherd; Jeremy S. Herman; Alison Sheridan; Sheena Fraser (Royal Society Open Science, 2016)
Rodents have important effects on contemporary human societies, sometimes providing a source of food but more often as agricultural pests, or as vectors and reservoirs of disease. Skeletal remains of rodents are commonly found in archaeological assemblages from around the world, highlighting their potential importance to ancient human populations. However, there are few studies of the interactions between people and rodents at such sites and most of these are confined to locations where rodents have formed a part of the recent diet. Here we compare the accumulation pattern of rodent remains from four locations within and adjacent to the renowned Neolithic site of Skara Brae, Orkney, showing that those within the settlement itself were the result of deliberate human activity. The accumulation and nature of burnt bones, incorporated over an extended period within deposits of household waste, indicate that rodents were used as a nutritional resource and may have been the subject of early pest control. We, therefore, provide the first evidence for the exploitation or control of rodents by the Neolithic inhabitants of Europe.